Investigating the Impact of Multicultural Literacy Components on the Development of Social and Emotional Skills among Upper Secondary School Students in District 2 of Ahvaz - Marmazi, Mohammad; Makvandi, Mohammad; Hosseinpour, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to determine the impact of multicultural literacy components on the development of social and emotional skills among upper secondary school students.Methods and Materials: This applied study employed a quantitative, descriptive-survey design. The statistical population consisted of all upper secondary school students in District 2 of Ahvaz during the 2024–2025 academic year (N = 12,584). Based on the Krejcie and Morgan sampling table, 295 students (150 males and 145 females) were selected through simple random sampling. Data were collected using the Multicultural Literacy Questionnaire (Ajam & Kadkhodaei, 2023), the Matson Social Skills Scale (1983), and the Emotion Regulation Questionnaire (Gross & John, 2003). The reliability of the instruments was confirmed using Cronbach’s alpha coefficients ranging from 0.82 to 0.88 in the present study. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics, including Pearson correlation and multiple linear regression analysis, through SPSS version 24.Findings: Regression analysis indicated that multicultural literacy had a positive and statistically significant effect on the development of social skills (R = .586, R² = .344, F(1,144) = 86.350, p < .05), explaining 34.4% of the variance in social skills. Furthermore, multicultural literacy demonstrated a positive and statistically significant effect on emotional skills (R = .570, R² = .325, F(1,144) = 80.380, p < .05), accounting for 32.5% of the variance in emotional skills. The standardized regression coefficients confirmed that higher levels of multicultural literacy were associated with higher levels of both social and emotional skill development.Conclusion: Enhancing students’ cognitive, affective, and behavioral dimensions of multicultural literacy may contribute to improved interpersonal functioning and adaptive emotion regulation within culturally diverse educational settings.